Gold Loading on Ion Exchange Resins in Non-Ammoniacal Resin-Solution Systems - Muslim, Abrar (Jurnal Rekayasa Kimia & Lingkungan, 2010)
The loading of gold using strong base anion exchange resin in non-ammoniac resin-solution (NARS) systems has been studied. The loading of gold onto ion exchange resins is affected by polythionate concentration, and trithionate can be used as the baseline in the system. The results also show that resin capacity on gold loading increases due to the increase in the equilibrium thiosulfate concentration in the NARS system. Gold loading performances show the need of optimization the equilibrium concentrations of thiosulfate in the NARS system.Keywords: equilibrium, gold loading, resin capacity, thiosulfate, trithionate